THE IMPLEMENTATION OF DYADIC ESSAY TECHNIQUE TO IMPROVE WRITING COMPETENCE FOR STUDENT INFORMATION SYSTEM PROGRAM - Marginingsih Marginingsih (LPPM Universitas Duta Bangsa Surakarta, 2015)
This research is to describe the implementation of learning writing through Dyadic Essay technique. The approach used in this study is a qualitative and quantitative approach. Design research is Classroom Action Research (CAR). This research is carried out in three cycles: cycle 1, cycle 2 and cycle 3. Data collection techniques are using test and non test. Data test includes writing text expository, while nontest includes form and questionnaire. The Population from this study is the student of Information Systems STMIK Duta Bangsa Surakarta at the first semester ofthe academic year 2014/2015.The result of the research shows that dyadic Essay is able to improve students' writing competence in writing structure expository text and classroom climate. Related to the structureof the text expository. The mean score of writing also improves from 66.25 to 80.7. Meanwhile, the improvement of classroom climate is indicated from: (1) writing activities are not so monotonous and more challenging; (2) the class is becoming an active class; and (3) the students are able to cooperate well with their group. Thus the application of Dyadic Essay can improve writing competence and classroom climate student of Information Systems at the first semester STMIKDuta Bangsa Surakarta.